2015
DOI: 10.1007/s13205-015-0339-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamic simulations of Escherichia coli l-asparaginase to illuminate its role in deamination of asparagine and glutamine residues

Abstract: Acute lymphocytic leukemia (ALL) is an outrageous disease worldwide. l-Asparagine (l-Asn) and l-Glutamine (l-Gln) deamination play a crucial role in ALL treatment. Role of Elspar® (l-asparaginase from Escherichia coli) in regulation of l-Asn and l-Gln has been confirmed by the other researchers through experimental studies. Therapeutic research against ALL remained elusive with the lack of information on molecular interactions of Elspar® with amino acid substrates. In the present study, using different docking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…This can be evidenced from the tables Table 1 and 2 that 28, 20 and 37% lower binding energies for L-asparagine for Lys43Ser, Ile70Leu and Ile101Val, respectively. Reddy et al, 10 and Oza et al, 15 reported similar trend of binding energies for both substrates with PDB ID: 1NNS and L-asparaginase of Withania sominefera respectively, however, these energy values are much lower compared to the selected model protein in the present study. This observation further confirms that selected mutant protein can be a promising candidate for ALL treatment.…”
Section: Fig 3: Ligands a L-asparagine And B L-glutaminesupporting
confidence: 56%
See 1 more Smart Citation
“…This can be evidenced from the tables Table 1 and 2 that 28, 20 and 37% lower binding energies for L-asparagine for Lys43Ser, Ile70Leu and Ile101Val, respectively. Reddy et al, 10 and Oza et al, 15 reported similar trend of binding energies for both substrates with PDB ID: 1NNS and L-asparaginase of Withania sominefera respectively, however, these energy values are much lower compared to the selected model protein in the present study. This observation further confirms that selected mutant protein can be a promising candidate for ALL treatment.…”
Section: Fig 3: Ligands a L-asparagine And B L-glutaminesupporting
confidence: 56%
“…Molecular dynamics simulations were carried out for independent wild-type protein as well as mutant Y306L using GROMACS 5.0.4 package along with GROMOS96 54a7 force field after solvation by simple point charge (SPC) keeping water model embedded in cubic simulation boxes with minimum edge distance of 10 Å. 10 The particle mesh Ewald method was used to treat long-range Coulomb interactions. During this, the bond lengths were constrained using the linear constraint solver (LINCS) algorithm.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Radius of gyration (R g) of both ACE2 complexes describes overall spread of molecule during a 20 ns MD run. A low Rg value indicates better structural integrity and folding behavior (Erva et al, 2016). A slight increase in Rg value of the intact ACE2-RBD complex was observed during first 5 ns of the run, then after no further drifts till end ( Figure 5, red line), however, the tACE2-RBD complex was found stable throughout the MD run ( Figure 5, violet line), which indicates its structural integrity.…”
Section: Simulation Showed Stability Of Tace2-rbd Complexmentioning
confidence: 96%
“…7 ). A low Rg value demonstrates better structural entirety and folding treatment [ 61 ]. Throughout the 30ns MD simulation, two complexes maintain a stable mean Rg of 2.2 nm for 6LU7-Bex and 3.2 nm for 6LZG-Ceti.…”
Section: Resultsmentioning
confidence: 99%